Kegagalan Kerjasama Sister City Kota Semarang dengan Kota Beihai - Putri, Selvinda Novintan; Adnan, Muhammad (Journal of Politic and Government Studies, 2017)
Abstract. One of the efforts to accelerate the development of the region/city is to establish cooperation, one of which is a Sister City partnership. This cooperation serves to overcome the problem by increasing bilateral and multilateral relations with utilizing an acceleration in the fields of science, technology and information, as well as the economy. Sister city cooperation is usually based on similar characteristics or similar conditions both regions/cities. The method used is a qualitative approach. With the data collection techniques used is to make observations (qualitative observations), qualitative interviews, collecting documents qualitative literature study and draw conclusions. Informants in this study is a Staff Section Cooperation Secretariat of Semarang and the Division Head of Spatial Planning and the Environment and Development Planning Agency of Semarang. The results showed that the reason for Semarang city government in cooperation sister city is because of the similarity of characteristics, have an attachment relationship with Beihai City as well as an interest in the work culture in China, one of the Beihai City. In the process of cooperation, in 2008 the MoU was signed, but after that there was no follow-up so that the cooperation stopped. As for the obstacles that led to the cooperation of the city government stalled Semarang is no initiative to make the idea of the idea of sustainability sister city program. While from the Beihai is none other than because of the policy of the leader at the time. Related to these findings, recommendations can be given is expected the two sides were able to overcome the obstacles that hinder cooperation during this sister city, such as giving the initiative in proposing or making the idea for the program and in giving further response so that communication and cooperation continue to run uninterrupted. Because if this cooperation run and managed then the benefits that can be by both cities will greatly impact the city of Semarang and Beihai own. Keywords: Cooperation, Sister City, Obstacle